Pregnant Plurisexual Women's Sexual and Relationship Histories across the Life Span: A Qualitative Study. Issue 3 (3rd July 2017) - Ross, Lori E.; Tarasoff, Lesley A.; Goldberg, Abbie E.; Flanders, Corey E.
ABSTRACT: Women identifying as plurisexual (i.e., those with the potential for attraction to more than one gender) experience unique issues associated with forming and maintaining intimate relationships. In particular, women identifying as plurisexual, unlike women identifying as monosexual, navigate choices and decisions related to the gender of their partners throughout their lifetime and may experience a variety of social pressures and constraints that influence these decisions. However, previous research on women's sexual and relationship trajectories has largely focused on adolescence and young adulthood, and therefore we know little about the experiences of women identifying as plurisexual at other life stages. The aim of this study was to profile the lifetime sexual and relationship trajectories of 29 different-gender partnered women identifying as plurisexual as described during pregnancy. The authors identified three primary types of trajectories: women who predominantly partnered with men, women who partnered with men and women about equally, and women who predominantly partnered with women, and found that various contextual factors, including heterosexism and monosexism, constrained women's opportunities for partnering with women. Implications for social and clinical interventions are discussed.